Arabinoxylan Isolated from Ispaghula Husk: A Better Alternative to Commercially Available Gelling Agents - Erum1, Alia; Bashir1, Sajid; Saghir2, Shazia; Hina1, Sadia; Batool1, Amna; Mahmood3, Tahir (Asian Journal of Chemistry, 2014)
Gelling behaviour of a polysaccharide arabinoxylan isolated from Ispaghula, Plantago ovata was investigated and effect of different factors such as concentration of gelling agent, temperature, pH and compatibility with solvents were also studied. Medicated paracetamol and acelofenac gel were formulated by using arabinoxylan as gelling agent. These gels were evaluated for rheological estimation, appearance, stability and compatibility studies and pharmacological effects. Arabinoxylan gelation was pH dependent, rapid gelation (less gelation time) at basic pH with very viscous gel, while at acidic pH (3) low viscosity gel was formed after 48 h. Similarly heating facilitates gelation by reducing gelation time. Arabinoxylan gel was compatible with water, 1 % propylene glycol and ethanol (30 %) while it was incompatible with 70 and 90 % ethanol. Paracetamol (oral) and acelofenac (topical) gels, containing arabinoxylan as gelling agent were homogenous, stable and showed pharmacological effects comparable to gels formulated with HPMC and tragacanth as gelling agent.